2012
DOI: 10.1016/j.seizure.2012.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of different anesthetic techniques on electrocorticography in patients undergoing epilepsy surgery – A bispectral index guided study

Abstract: In our study optimal ECoG recordings were possible with use of either isoflurane or propofol. Addition of nitrous oxide to either of the anesthetic regimens suppressed the ECoG score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…Despite its widespread usage, there are still controversies regarding its utility especially keeping in mind its short period of application. [27282930] It also should be kept in mind that any electrode used potentially records from millions of neurons, for example, a circular electrode of the EcoG grid sits over 10 6 neurons, each having about 10 4 connections. Thus, this is equivalent to hanging a microphone among a population of 1 million people, each talking to 10,000 persons!…”
Section: Tools To Study Epileptogenic Networkmentioning
confidence: 99%
“…Despite its widespread usage, there are still controversies regarding its utility especially keeping in mind its short period of application. [27282930] It also should be kept in mind that any electrode used potentially records from millions of neurons, for example, a circular electrode of the EcoG grid sits over 10 6 neurons, each having about 10 4 connections. Thus, this is equivalent to hanging a microphone among a population of 1 million people, each talking to 10,000 persons!…”
Section: Tools To Study Epileptogenic Networkmentioning
confidence: 99%
“…Added to the above, they showed that the addition of N 2 O reduced the epileptiform activity in the iECoG. 13 Another study, which included propofol-remifentanil or sevofluraneremifentanil groups, did not find any differences between groups in spike frequency, spike amplitude, or number of spiking leads. Decreasing BIS levels in both groups enhanced epileptogenic spike frequency and amplitude with the same location and number of spiking leads.…”
Section: Discussionmentioning
confidence: 99%
“…12 It is measured in a score from 0 to 100 based on an algorithm empirically calculated based on changes observed in the EEG pattern during general anesthesia; a score between 40 and 60 correlates with a low probability of intraoperative awareness. 11,13 It has been proposed that the BIS may be used to titrate volatile anesthetics more precisely to individual requirements. The aforementioned avoids exposure to unnecessarily high concentrations of anesthetics while minimizing the likelihood of awareness during anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…During epilepsy surgery, monitoring the subdural electrocorticogram (ECoG) is a common procedure used to identify the location and the extent of epileptogenic zone, as well as to guide the extent of resection. As anesthetics influence ECoG in patients with epilepsy , the choice of anesthetics that do not suppress epileptiform discharges is important to determine the area of resection. Although general anesthetic techniques for epilepsy surgery remain largely empiric, typically institution‐specific and sparsely described in literature, sevoflurane is one of the anesthetics used for this purpose .…”
Section: Introductionmentioning
confidence: 99%
“…Surgical intervention in a pediatric population leads to improved outcomes ; however, few studies have examined the effect of general anesthesia on ECoG in pediatric patients with epilepsy . As sevoflurane induces epileptic discharge in children as well as in adults , it is important to elucidate the effect of inhalational anesthetics on ECoG in children.…”
Section: Introductionmentioning
confidence: 99%